Association of hospital structures with mortality from ruptured abdominal aortic aneurysm. Issue 5 (19th February 2015) - Ozdemir, B. A.; Karthikesalingam, A.; Sinha, S.; Poloniecki, J. D.; Vidal‐Diez, A.; Hinchliffe, R. J.; Thompson, M. M.; Holt, P. J. E.
<x xml:space="preserve">Abstract</x> Background There is significant variation in the mortality rates of patients with a ruptured abdominal aortic aneurysm (rAAA) admitted to hospital in England. This study sought to investigate whether modifiable differences in hospital structures and processes were associated with differences in patient outcome. Methods Patients diagnosed with rAAA between 2005 and 2010 were extracted from the Hospital Episode Statistics database. After risk adjustment, hospitals were grouped into low‐mortality outlier, expected mortality and high‐mortality outlier categories. Hospital Trust‐level structure and process variables were compared between categories, and tested for an association with risk‐adjusted 90‐day mortality and non‐corrective treatment (palliation) rate using binary logistic regression models. Results There were 9877 patients admitted to 153 English NHS Trusts with an rAAA during the study. The overall combined (operative and non‐operative) mortality rate was 67·5 per cent (palliation rate 41·6 per cent). Seven hospital Trusts (4·6 per cent) were high‐mortality and 15 (9·8 per cent) were low‐mortality outliers. Low‐mortality outliers used significantly greater mean resources per bed (doctors: 0·922 versus 0·513, P < 0·001; consultant doctors: 0·316 versus 0·168, P < 0·001; nurses: 2·341 versus 1·770, P < 0·001; critical care beds: 0·045 versus 0·019, P < 0·001; operating theatres: 0·027 versus 0·019, P = 0·002) and performed more fluoroscopies (mean 12·6 versus 9·2 per bed; P = 0·046) than high‐mortality outlier hospital Trusts. On multivariable analysis, greater numbers of consultants, nurses and fluoroscopies, teaching status, weekday admission and rAAA volume were independent predictors of lower mortality and, excluding rAAA volume, a lower rate of palliation. Conclusion The variability in rAAA outcome in English National Health Service hospital Trusts is associated with modifiable hospital resources. Such information should be used to inform any proposed quality improvement programme surrounding rAAA.